The Effects of Reverse Nordic Exercise Training on Measures of Physical Fitness in Youth Karate Athletes - Raja Bouguezzi; Senda Sammoud; Yassine Negra; Younés Hachana; Helmi Chaabene (Journal of Functional Morphology and Kinesiology)
Background: In karate, the ability to execute high-velocity movements, particularly kicks and punches, is heavily dependent on the strength and power of the lower limb muscles, especially the knee extensors. As such, this study aimed to evaluate the effects of an 8-week eccentric training program utilizing the reverse Nordic exercise (RNE) integrated into karate training compared with regular karate training only on measures of physical fitness in youth karate athletes. Methods: Twenty-seven youth karatekas were recruited and allocated to either RNE group (n = 13; age = 15.35 ± 1.66 years; 7 males and 6 females) or an active control group ([CG]; n = 14; 7 males and 7 females; age = 15.30 ± 1.06 years). To track the changes in measures of physical fitness before and after training, tests to assess linear sprint speed (i.e., 10 m), change of direction (CoD) speed (i.e., modified 505 CoD), vertical jumping (i.e., countermovement jump [CMJ] height) and horizontal jumping distance (i.e., standing long jump [SLJ]), and lower-limb asymmetry score (i.e., the difference between SLJ-dominant and non-dominant legs) were carried out. Results: The results indicated significant group-by-time interactions in all measures of physical fitness (effect size [ES] = 1.03 to 2.89). Post-hoc analyses revealed significant changes in the RNE group across all performance measures (effect size [ES] = 0.33 to 1.63). Additionally, the asymmetry score exhibited a moderate decrease from pre to posttest (∆46.96%, ES = 0.64). In contrast, no significant changes were observed in the CG across all fitness measures. Moreover, the individual response analysis indicated that more karatekas from the RNE group consistently achieved improvements beyond the smallest worthwhile change threshold across all fitness measures. Conclusions: In summary, RNE training is an effective approach to enhance various physical fitness measures besides lower-limb asymmetry scores in youth karatekas and is easy to incorporate into regular karate training. Practitioners are therefore encouraged to consistently integrate RNE training to enhance essential physical fitness components in young karatekas.